REPLICATION OF MURINE MITOCHONDRIAL DNA FOLLOWING IRRADIATION - Zhang, Hengshan (2009)
The effect of radiation on the mitochondrial genome in vivo is largely unknown. Though mitochondrial DNA (mtDNA) is vital for cellular survival and proliferation, it has little DNA repair machinery compared with nuclear DNA (nDNA). A better understanding of how radiation affects mtDNA should lead to new approaches for radiation protection. We have developed a new system using real-time PCR that sensitively detects the change in copy number of mtDNA compared with nDNA. In each sample, the DNA sequence coding 18S rRNA served as the nDNA reference in a run simultaneously with a mtDNA sequence. Small bowel collected 24 hours after 2 Gy or 4 Gy total body irradiation (TBI) exhibited increased levels of mtDNA compared with control mice. A 4 Gy dose produced a greater effect than 2 Gy. Similarly, in bone marrow collected 24 hours after 4 Gy or 7 Gy TBI, 7 Gy produced a greater response than 4 Gy. As a function of time, a greater effect was seen at 48 hours compared with 24 hours. In conclusion, we found that radiation increased the ratio of mtDNA:nDNA and that this effect seems to be tissue independent and seems to increase with radiation dose and duration following radiation exposure.